MoreMilkIT - Household baseline survey - Omore, Amos; Baltenweck, Isabelle; Kariuki, Eunice; Njehu, Alice; Githinji, Julius (International Livestock Research Institute, 2015)
More milk by and for the poor: Adapting dairy market hubs for pro-poor smallholder value chains in Tanzania (MoreMilkIT)